Effect of Gold/Fe3O4 Nanoparticles on Biocompatibility and Neural Differentiation of Rat Olfactory Bulb Neural Stem Cells. (18th September 2013) - Wang, Menghang; Li, Zhou; Qiao, Huiting; Chen, Luoping; Fan, Yubo
Abstract : Transplantation of stem cells is a potential clinical therapy for repair of central nervous system injury. However, transplanted cells are especially difficult to arrive at the targeted site because of poor survival rate and low efficiency. Recently, gold nanoparticles (NPs) and Iron oxide NPs, as novel nanoparticles, have been used as auxiliary strategy to investigate the nervous system diseases. The present study demonstrates the effect of Gold/Fe3 O4 NPs on biocompatibility and differentiated properties of rat olfactory bulb stem cells. Cell viability was assumed by MTT test and cytotoxicity was assessed by Hoechst 33342-PI stain. Cells were cultured at Gold/Fe3 O4 NPs concentration range of 40 to 200 μ g/10 4 cells for 24 h. Differentiation was assessed by NSE (a neuronal marker) stain. Results showed that Gold/Fe3 O4 NPs at the concentrations of 40 μ g/10 4 cells enhanced cell viability and decreased the cell death rate. Furthermore, the differentiation properties were detected by NSE marker. These findings suggest that Gold/Fe3 O4 NPs may thus be used as new nanotechnologies in stem-cell-based transplantation therapies for diagnosis and treatment of central nervous system diseases.